Nigella sativa: A Potential Antiosteoporotic Agent. (3rd September 2012) - Shuid, Ahmad Nazrun; Mohamed, Norazlina; Mohamed, Isa Naina; Othman, Faizah; Suhaimi, Farihah; Mohd Ramli, Elvy Suhana; Muhammad, Norliza; Soelaiman, Ima Nirwana
Abstract : Nigella sativa seeds (NS) has been used traditionally for various illnesses. The most abundant and active component of NS is thymoquinone (TQ). Animal studies have shown that NS and TQ may be used for the treatment of diabetes-induced osteoporosis and for the promotion of fracture healing. The mechanism involved is unclear, but it was postulated that the antioxidative, and anti-inflammatory activities may play some roles in the treatment of osteoporosis as this bone disease has been linked to oxidative stress and inflammation. This paper highlights studies on the antiosteoporotic effects of NS and TQ, the mechanisms behind these effects and their safety profiles. NS and TQ were shown to inhibit inflammatory cytokines such as interleukin-1 and 6 and the transcription factor, nuclear factor κ B. NS and TQ were found to be safe at the current dosage for supplementation in human with precautions in children and pregnant women. Both NS and TQ have shown potential as antiosteoporotic agent but more animal and clinical studies are required to further assess their antiosteoporotic efficacies.